Hubungan Antara Rasio Agregat dan Volumetrik dalam Menentukan Kualitas Perkerasan Jalan - Fatardhoo, Abroor Kissraya; Cahyono, Andri Dwi; Hidiyati, Evita Fitrianis; Zakaria, Ahmad Lufi; Pratama, Ahmad Figur; Nugraha, Muh Wahyu Dian; Febriansyah, Yanwar; Pratama, Diva Iga (Jurnal Manajemen Teknologi & Teknik Sipil, 2024)
Road pavement quality is a critical factor in supporting a country's mobility and economy. Around 40% of the road length in Indonesia suffers damage, including permanent deformation and early cracking. To overcome road damage, it is important to know the pavement quality parameters such as Voids in Mineral Aggregate (VMA), Voids in Mix (VIM), and Voids Filled with Bitumen (VFB), along with the factors that influence them, such as material characteristics. This study aims to determine the effect of the fine and coarse aggregate ratio on volumetric parameters in asphalt mixtures, including VIM, VMA, and VFB. The experimental method was carried out on four samples. Aggregate characteristic tests were carried out, including gradation tests. Volumetric tests were carried out on each sample with asphalt content of 4%, 4.5%, and 5%. The research results show that the smaller fine-to-coarse aggregate ratio would increase the VMA and VIM values and decrease the VFB value. Aggregate ratio significantly affects volumetric parameters, which shows the importance of selecting aggregate with the right size distribution and determining the right ratio to achieve optimal pavement performance. The results of this study can be used as a practical guide for optimizing asphalt mix design with better quality and durability.